KUANTITAS PENGGUNAAN ANTIBIOTIK PADA PASIEN BEDAH ORTOPEDI RSUP DR. KARIADI SEMARANG - Anangga Haryanto; Agus Priambodo; Endang Sri Lestari (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Background : The development of technology nowadays gives a lot of benefits, however it creates some negative effects such as decreasing physical activity that can cause obesity in the population. Obesity creates some chronic diseasessuch as cancer and heart disease. The composition of body consists of fat mass and fat free mass. Zumba is one of the most popularphysical exercise that can decrease percentage of body fat.Aim : To observe the effect of Zumba exercise on body fat percentage in young females.Method: This is an analytic observasional study with cross sectional design. Research subjects were females aged 20-25 years who experienced Zumba exercise (n=24). The percentage of body fat was measured with Bioelectric Impedance Analysis (Glass Body Analyzer 835) weight scales. Correlation between the period of Zumba exercise and body fat percentage was analyzed using Spearman’s rho correlation test.Results: The body fat percentage in subjects who were conducted Zumba for ≥8 weeks was lower compared to subjects who were conducted Zumba for <8 weeks. The body fat percentage average in subjects who experienced Zumba for<8 weeks is 31,97 ± 5,27 with 25,7 was the lowest score and 42,9 was the highest score, and the average percentageof subjects who experienced Zumba for ≥8 weeks was 27,47±2,96 with 22,6 was the lowest score and 42,9 was the highest. There was a negative correlation with moderate degree of body fat percentage with Zumba exercise (r=-0,421; p=0,04) in Spearman’s rho test.Conclusion : The study found thedifferences between the average of body fat percentage in subjectswhoexperiencedZumbaexercisefor<8 weeks and≥8weeks. This study also showed a negative correlation with moderate degree between body fat percentage and Zumba exercise period.